2015
DOI: 10.2147/ijn.s84656
|View full text |Cite
|
Sign up to set email alerts
|

Anti-transferrin receptor-modified amphotericin B-loaded PLA–PEG nanoparticles cure Candidal meningitis and reduce drug toxicity

Abstract: Fatal fungal infections in central nervous system (CNS) can occur through hematogenous spread or direct extension. At present, hydrophobic amphotericin B (AMB) is the most effective antifungal drug in clinical trials. However, AMB is hydrophobic and therefore penetrates poorly into the CNS, and therapeutic levels of AMB are hard to achieve. The transferrin receptor (TfR/CD71) located at the blood–brain barrier mediates transferrin transcytosis. In order to enhance the receptor-mediated delivery of AMB into CNS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…To date, several antifungal ( Leal et al, 2015 ) and antibacterial ( Gubernator et al, 2007 ) drugs have been given as encapsulated liposomal formulations to enhance their therapeutic index. In particular, Amp B has been studied exclusively with the aim to reduce its toxicity and side-effects by entrapping into lipid complex and multilamellar (ML) vesicles ( Tang et al, 2015 ). The outermost bilayer of multilamellar phospholipid vesicles fuses with the plasma membrane of the cell, providing increased surface area and invagination of the excess plasma membrane ( Batzri and Korn, 1975 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, several antifungal ( Leal et al, 2015 ) and antibacterial ( Gubernator et al, 2007 ) drugs have been given as encapsulated liposomal formulations to enhance their therapeutic index. In particular, Amp B has been studied exclusively with the aim to reduce its toxicity and side-effects by entrapping into lipid complex and multilamellar (ML) vesicles ( Tang et al, 2015 ). The outermost bilayer of multilamellar phospholipid vesicles fuses with the plasma membrane of the cell, providing increased surface area and invagination of the excess plasma membrane ( Batzri and Korn, 1975 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, these nanoparticles have to face competition with the endogenous ligands of these receptors. This problem can be avoided by using antibodies against transferrin receptors, i.e., OX26, which bind to another binding site of the receptor [74, [80][81][82][83]. However, it has been shown that OX26 is mostly associated with brain capillaries through the brain parenchyma [117].…”
Section: Surface Functionalizationmentioning
confidence: 99%
“…Polylactic acid (PLA) is a synthetic biodegradable polymer that has been approved by the U.S. Food and Drug Administration (FDA) for medical applications [18, 19]. However, because of its weak hydrophilicity, excessively long degradation time, and low drug loading of polar drugs [20, 21], PLA’s applications are limited. To overcome these shortcomings, PEG was combined with PLA to form a block co-polymer in this study [2224].…”
Section: Discussionmentioning
confidence: 99%